2018
DOI: 10.1038/sj.bdj.2018.171
|View full text |Cite
|
Sign up to set email alerts
|

Tooth wear risk assessment and care-planning in general dental practice

Abstract: Objective To assess charting, risk assessment and treatment-planning of tooth wear between recently qualified and experienced dentists in general dental practice.Design Service evaluation.Setting Multi-setting evaluation of three mixed NHS/Private general dental practices in North-East London.Methods The clinical notes of new patient examinations on dentate adults presenting from the 1 October 2016 to 31 December 2016 were audited collecting data on tooth wear charting, risk assessment and treatment planning. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
(22 reference statements)
0
7
1
Order By: Relevance
“…Implementation of an easy-to-use index such as BEWE into patient records would be beneficial; this would serve clinicians in the evaluation and follow-up of ETW. Opposite to the findings of O'Toole et al [9], respondents' working experience had no association with the recording practices. 2) 52 (7.7) n¼the number of dentists responding to each question, multiple choices were allowed.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Implementation of an easy-to-use index such as BEWE into patient records would be beneficial; this would serve clinicians in the evaluation and follow-up of ETW. Opposite to the findings of O'Toole et al [9], respondents' working experience had no association with the recording practices. 2) 52 (7.7) n¼the number of dentists responding to each question, multiple choices were allowed.…”
Section: Discussioncontrasting
confidence: 87%
“…Epidemiologic studies suggest an increasing prevalence and severity of ETW among children and adolescents [5,6]. However, literature suggests that among clinical dental practitioners, there appears to be a need for enhancing awareness and knowledge about ETW and how to deal with it [7][8][9][10]. A large proportion of dentists are reported to advise their patients about ETW only occasionally or rarely [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…An earlier study carried out in general dental practice evaluated the extent to which recently‐graduated and experienced dentists recorded, assessed risk, and planned non‐operative strategies for erosive tooth wear [24]. These authors reported that experienced dentists were significantly less likely to both assess risk and propose non‐operative strategies for erosive tooth wear.…”
Section: Discussionmentioning
confidence: 99%
“…53 This lack of severe biological implications of wear on teeth draws into question the merit of treatment. Multiple epidemiological studies have shown that there is an impact of severe tooth wear on quality of life and this has been observed to be related primarily to aesthetics, 54,55 not function although the quality of evidence for this is low. One investigative clinical study aimed to identify the impact of prosthodontic rehabilitation on quality of life.…”
Section: Focus Question 3: What Happens To Teeth As They Wear?mentioning
confidence: 99%